Maturity Model of Village Owned Enterprise (VOE) as Social Business in Indonesia: Comparative Study of the VOE in The Tourism Sector - Wahyono, Tri; Chan, Arianis; Karlina, Nina (Journal of Ecohumanism, 2025)
Village-owned enterprises (VOEs) are expected to play an important role in promoting local economic growth by leveraging local resources and engaging community participation to foster sustainable development. The Indonesian government has supported the establishment of VOE since 1999; nevertheless, its impact on enhancing village original income and social benefits is still limited. Significant concerns exist over the potential of VOE to function as a social enterprise that promotes profit generation as well as social benefit. This study employs a descriptive comparative methodology to analyze the growth trajectory of VOE as a social enterprise in Indonesia. The study focused on three VOEs, which are VOE Tirta Mandiri, VOE Sumber Sejahtera, and VOE Kembang Kuning. The results of this study showed that VOE evolution as a social enterprise follows five stages: initial, infrastructure, defined, managed, and optimized. There are three dimensions to each stage: the input, which is made up of two variables, such as leadership and village potential; the process, which is made up of three variables, such as efficiency, participation, and innovation; and the outcome, which is made up of three variables, such as profit, social benefits, and resilience. These five levels, three dimensions, and eight variables are the components of the maturity model for VOE as a social enterprise in Indonesia. This maturity model serves as an important lesson for countries in the Global South in fostering sustainable village development.